Manajemen praktek kerja lapangan pada program keahlian teknik komputer dan jaringan di SMK Prima Sejahtera Kotamobagu - Mamesah, Sheyla Fitriananda; Sumual, Shelty D. M.; Lengkong, Jeffry S. J. (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study was to determine and analyze the management of Field Work Practice (PKL) Computer and Network Engineering Expertise Program at SMK Prima Sejahtera Kotamobagu, in terms of Planning, Implementation and Evaluation. This research is a type of qualitative research with research procedures that produce descriptive data. The methods used by researchers to collect data are observation, interviews and documentation studies. The subjects of this research are the Principal, Deputy for Public Relations, Head of the Computer and Network Engineering Department (TKJ), Supervising Teacher. After the data is collected, the data is analyzed including data reduction, and conclusion drawing. Based on the results of the study, it shows that the PKL planning stage includes: 1) PKL committee formation and coordination, 2) Industry mapping, 3) Administrative preparation (such as: making submission letters and submission procedures, making submission and withdrawal letters, making PKL activity schedules), 4) Determination of PKL place, 5) Debriefing. The stages of implementation activities: 1) Delivery of PKL students, 2) PKL implementation process in the Business World / Industrial World (DUDI), 3) PKL program monitoring, 4) Journal preparation of daily PKL activities, and 5) Withdrawal of PKL students. The PKL evaluation stage includes: 1) Completion of the journal which is carried out after the pick-up of students, 2) PKL assessment based on the results of coordination by industry and school supervisors and based on the results of reports/journals.